(untitled) (Journal of Mental Health & Well-being, 2025)
Neuropsychiatric disease is a major global health burden, and an important part of its challenge is the complexity of its etiologies and the modest response to many therapy options. Conventional treatments typically palliate rather than address the underlying disease process, often resulting in residual disability for many patients. Stem cell therapeutic approach, on the basis of the distinctive characteristics of undifferentiated cells, is an attractive biotechnological horizon for treatment of these diseases. The aim of this review is to describe the current state of the field, covering the basics of stem cell biology, the various applications for modeling/neuropsychiatric disease understanding, and neural repair. It also explores the significant technical, ethical, and economic challenges that need to be addressed. Lastly, it reviews up-to-date advances in preclinical and clinical applications, future perspectives and translational routes, such as combination with the latest technologies and regulatory aspects, to bring these potential therapies closer to clinical reality.